2022
DOI: 10.1002/aic.17631
|View full text |Cite
|
Sign up to set email alerts
|

Cuprous‐based composite ionic liquids for the selective absorption of CO: Experimental study and thermodynamic analysis

Abstract: Three cuprous-based composite ionic liquids (ILs) [EimH][OAc]-xCuOAc (x = 0.5, 0.6, 0.7) were prepared and employed for efficient absorption of CO. It is shown that the cuprous composite IL [EimH][OAc]-0.6CuOAc exhibited the largest absorption capacity for CO (0.031 g/g at 293.15 K and 1 bar) and had a record CO/N 2 selectivity of 967, which is better than most of common ILs and solvents reported in the literature. The results of Fourier transform infrared (FTIR) spectra, electrospray ionization mass spectrome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 37 publications
1
15
0
Order By: Relevance
“…It is found that the quaternary DES [Emim]­Cl-CuCl-ZnCl 2 -EG showed an extremely low capacity in the capture of pure N 2 or CO 2 or H 2 in comparison with efficient absorption of CO. The ideal absorption selectivities of CO 2 /CO, H 2 /CO, and N 2 /CO were calculated to be 23, 18, and 943 at 298.2 K and 1.0 bar, respectively, indicating that [Emim]­Cl-CuCl-ZnCl 2 -EG is much better than many reported DESs or ILs in the literature. ,,,, The quaternary DES [Emim]­Cl-CuCl-ZnCl 2 -EG thus shows remarkable potential for selective absorption of CO from other competitive gases.…”
Section: Resultsmentioning
confidence: 95%
See 4 more Smart Citations
“…It is found that the quaternary DES [Emim]­Cl-CuCl-ZnCl 2 -EG showed an extremely low capacity in the capture of pure N 2 or CO 2 or H 2 in comparison with efficient absorption of CO. The ideal absorption selectivities of CO 2 /CO, H 2 /CO, and N 2 /CO were calculated to be 23, 18, and 943 at 298.2 K and 1.0 bar, respectively, indicating that [Emim]­Cl-CuCl-ZnCl 2 -EG is much better than many reported DESs or ILs in the literature. ,,,, The quaternary DES [Emim]­Cl-CuCl-ZnCl 2 -EG thus shows remarkable potential for selective absorption of CO from other competitive gases.…”
Section: Resultsmentioning
confidence: 95%
“…This suggests that the π-complexation between CO and Cu + species in [Emim]­Cl-CuCl-ZnCl 2 -EG is relatively slow, requiring enough and long contact time. In addition, the CO uptake capacities and rates of [Emim]­Cl-CuCl and [Emim]­Cl-CuCl-ZnCl 2 -EG were compared with those of reported ILs and DESs such as [Bmim]­[Tf 2 N], [P 4448 ]­[Pen], [EimH]­[CuCl 2 ], [TEA]­[CuCl 2 ], [EimH]­[OAc]–0.6CuOAc, and [BimH]­Cl-CuCl-1.0ZnCl 2 . ,− ,, As seen from Table , the solubility of CO in [Emim]­Cl-CuCl-ZnCl 2 -EG at 298.2 K was 1–2 orders higher than the cases of all the current reported absorbents. The CO absorption equilibrium time of 20 min for binary DES [Emim]­Cl-CuCl was comparable to that of the reported composite IL [EimH]­[OAc]–0.6CuOAc.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations